The Effects of an In Vitro Oocyte Maturation System and Chlorogenic Acid Supplementation during Embryo Culture on the Development of Porcine Cloned Embryos Derived from Native Vietnamese Ban Pigs - Thanh Van Nguyen; Lanh Thi Kim Do; Ngoc-Anh Thi Nguyen; Kazuhiro Kikuchi; Tamas Somfai; Takeshige Otoi (Veterinary Medicine International)
The aim of this study was to improve the production efficiency of Vietnamese native Ban pig embryos using somatic cell nuclear transfer (SCNT). Fibroblast cells from Ban pigs were injected into the enucleated cytoplasts of crossbred gilts, and the reconstructed embryos were subsequently cultured. In the first experiment, cytoplasts were isolated from oocytes matured in either a defined porcine oocyte medium (POM) or in TCM199 medium supplemented with porcine follicular fluid. Both media were supplemented with gonadotropic hormones, either for the first 22 h of in vitro maturation (IVM) or for the entire 44 h of IVM. In the second experiment, the reconstructed SCNT embryos were cultured with or without 50 μM chlorogenic acid (CGA). Furthermore, this study examined parthenogenetic embryos. The IVM medium and duration of hormone treatment did not affect embryo development. CGA supplementation to the culture medium significantly increased blastocyst formation rates in parthenogenetic embryos but not in SCNT embryos. However, CGA supplementation significantly reduced the apoptotic index in blastocysts regardless of embryo source. In conclusion, the IVM method did not affect SCNT embryo production, while CGA supplementation during embryo culture improved the quality of SCNT embryos in indigenous pig breeds.